2009
DOI: 10.3109/00048670903179103
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of community treatment orders for treatment of schizophrenia with oral or depot antipsychotic medication: changes in problem behaviours and social functioning

Abstract: A CTO may contribute to improved outcomes related to patient quality of life. This may be seen to mitigate concerns about infringement of civil rights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Similarly in the United Kingdom, the proportion of LAI antipsychotic users (64%) was also higher than oral antipsychotic users . These findings are consistent with previous studies identifying an association between LAI antipsychotic use among CTO recipients . While the relative cost‐effectiveness of LAI antipsychotics remains unknown , use of LAI antipsychotics are beneficial in reducing relapse .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly in the United Kingdom, the proportion of LAI antipsychotic users (64%) was also higher than oral antipsychotic users . These findings are consistent with previous studies identifying an association between LAI antipsychotic use among CTO recipients . While the relative cost‐effectiveness of LAI antipsychotics remains unknown , use of LAI antipsychotics are beneficial in reducing relapse .…”
Section: Discussionsupporting
confidence: 87%
“…Previous Australian studies have established that there is a direct association between the use of CTOs and LAI antipsychotics (), with individuals issued a CTO in Victoria more than twice as likely to be prescribed a LAI than an oral antipsychotic . Furthermore, compared with a rate of approximately 30% of LAI antipsychotic use among individuals prescribed antipsychotics , rates of 47% and 63% have been observed among individuals with schizophrenia receiving a CTO in recent studies conducted in Victoria, Australia, and the United Kingdom, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few randomised controlled studies were evaluated in a Cochrane review, which concluded that such treatments may not be an effective alternative to standard care [13]. Nonetheless, indications for a favourable effect on quality of life and reduced episodes of homelessness and aggression have been found [10]. Our findings underline the urgent need for more research on this important and ethical controversial topic.…”
Section: Involuntary Treatmentmentioning
confidence: 80%
“…La búsqueda sistemática encontró un artículo que respondió la pregunta PICO de forma indirecta. Es el estudio de Ingram y colaboradores (2009) (24) quienes examinaron si el uso de community treatment orders (CTO) en Australia puede estar asociado con una reducción de problemas de conducta y mejoras en funcionalidad social. Para ello, diseñaron un estudio observacional retrospectivo naturalista de imágenes de casos, con cada caso sirviendo como su propio control en 212 pacientes.…”
Section: De La Evidencia a La Práctica Clínicaunclassified